Functional anterior pituitary generated in self-organizing culture of human embryonic stem cells - Chikafumi Ozone; Hidetaka Suga; Mototsugu Eiraku; Taisuke Kadoshima; Shigenobu Yonemura; Nozomu Takata; Yutaka Oiso; Takashi Tsuji; Yoshiki Sasai (Nature Communications, 2016)
It is difficult to generate functional human anterior pituitary tissues in vitro. Here, Ozone et al. generate human anterior pituitary from embryonic stem cells by recapitulating in vivodevelopment, and demonstrate this tissue secretes hormones and rescues hypopituitarism when grafted into mice.